Performance Analysis of D-MoSK Modulation in Mobile Diffusive-Drift Molecular Communication Relay System (Global Journal of Computer Science and Technology, 2022)
Molecular communication (MC) is a new wireless communication technology, which uses molecules as information carriers. Diffusion-based MC is one of the most common MC methods. With the increase of diffusion distance, the molecular signal attenuation is serious, so the traditional communication technology of relay is introduced into the MC system. In this work, a mobile diffusive-drift MC relay model is investigated, in which the depleted molecule shift keying (D-MoSK) modulation is used. The closed-form expression of symbole error rate (SER) and the channel capacity are derived, meanwhile the impacts of several crucial parameters on the performance are discussed comprehensively.
Keywords: molecular communication; relay; diffusivedrift; symbol error rate; depleted molecule shift keying